Pharmacokinetic Variability of Vancomycin Under Different Anesthetic Conditions in Septic ICU Patients with Augmented Renal Clearance - Muhammad Umer Javaid, Faheed ul Haque, Zain Aamir, Ali Nawaz Bijarani, Sidra Zahid, Nida Ayesha (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Septic critically ill patients exhibiting augmented renal clearance (ARC) present a clinicallyimportant challenge for vancomycin dosing. This prospective observational study evaluated pharmacokinetic variability of vancomycin